2000
DOI: 10.1177/002215540004800709
|View full text |Cite
|
Sign up to set email alerts
|

Protease-elicited TUNEL Positivity of Non-apoptotic Fixed Cells

Abstract: The appearance of free DNA ends in the chromatin is usually considered an indication of advanced apoptosis. Unexpectedly, the nuclei of non-apoptotic cells derived from mouse thymuses could be specifically labeled by terminal transferase after proteinase K treatment of the fixed, cytocentrifuged samples. Artifactual mechanical or contaminating nucleolytic factors have been ruled out as players in the generation of free DNA ends. The phenomenon was detected in both formaldehyde- and ethanol-fixed specimens, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…Focusing on the TUNEL method for apoptosis assessment, it has been widely demonstrated that it can produce an intrinsic nonspecific labelling. This does not represent a background staining but a binding with DNA fragments produced by endogenous cytoplasmic endonuclease that is physiologically present, or by antigen retrieval pretreatment [10-12,22,23]. In the present study, the non-specific TUNEL labelling was cytoplasmic, patchy, and hazy, with intense peripheral membranous positivity.…”
Section: Discussioncontrasting
confidence: 45%
“…Focusing on the TUNEL method for apoptosis assessment, it has been widely demonstrated that it can produce an intrinsic nonspecific labelling. This does not represent a background staining but a binding with DNA fragments produced by endogenous cytoplasmic endonuclease that is physiologically present, or by antigen retrieval pretreatment [10-12,22,23]. In the present study, the non-specific TUNEL labelling was cytoplasmic, patchy, and hazy, with intense peripheral membranous positivity.…”
Section: Discussioncontrasting
confidence: 45%
“…The lack of labeling by TdT in solution is also unexpected in view of the fact that cytocentrifuged, fixed cells can become TUNEL‐positive upon proteinase treatment [Gál et al, 2000]. However, a weak but well detectible end‐labeling of ∼50 kb DNA prepared from previously ethanol‐fixed cells by TdT was observed, while parallel samples of non‐fixed origin were completely negative (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…Based on this view, random breakage of the long DNA molecules would be expected. Several observations, however, run counter this view: the average size of DNA molecules obtained during protein denaturing treatments of lysates prepared from normal cells without embedding is always around ∼50 kb (forming in some cellular systems, a rather well‐focused band, unexplained by a compression artifact, see Szabó et al, 1990); loop‐size chromatin fragmentation can also be observed upon rapid alkaline lysis of live cells in suspension [Szabó and Bacsó, 1996], and when DNA is isolated from fixed cells [Gál et al, 2000]; this phenomenon has also been demonstrated when agarose plugs containing deproteinized chromatin of mammalian or yeast cells are melted to 60–85°C [Varga et al, 1999]. Based on the stepwise, large‐scale chromatin fragmentation observed upon digestion of isolated nuclei with endogenous nucleases and after treatment with topoisomerase II poisons it was suggested that chromatin loops contain approximately 50 kb of DNA [Kokileva, 1988; Filipski et al, 1990].…”
mentioning
confidence: 99%
“…The samples were unmasked using citric buffer boil [16] instead of proteinase K unmasking, which can generate false positives [28]. Positive cells labelled with FITC were counted and presented as a percentage of all (DAPI stained) cells in selected zones of the growth plate.…”
Section: Methodsmentioning
confidence: 99%